2003
DOI: 10.1197/s1069-6563(03)00350-6
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Severity Index Triage Algorithm Version 2 Is Reliable and Valid

Abstract: ESI v. 2 triage produced reliable, valid stratification of patients across seven sites. ESI triage should be evaluated as an ED casemix identification system for uniform data collection in the United States and compared with other major ED triage methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(115 citation statements)
references
References 38 publications
(54 reference statements)
10
96
1
8
Order By: Relevance
“…According to the results of the current study, higher acuity of ESI triage level was associated with higher mortality rate ( Table 1). This finding is consistent with the results of previous studies in this regard (7,20,21). Higher correlation coefficient of hospitalization and mortality rates among male patients could be due to the over-triaging of female patients or under-triaging of male patients.…”
Section: Discussionsupporting
confidence: 83%
“…According to the results of the current study, higher acuity of ESI triage level was associated with higher mortality rate ( Table 1). This finding is consistent with the results of previous studies in this regard (7,20,21). Higher correlation coefficient of hospitalization and mortality rates among male patients could be due to the over-triaging of female patients or under-triaging of male patients.…”
Section: Discussionsupporting
confidence: 83%
“…During most of the study period, acuity was assessed using the Emergency Severity Index, previously shown to be reliable and valid. 28,29 During the first eight months of our study period, acuity was assessed using the Canadian Triage and Acuity Scale, which has also been shown to be reliable. 30 Chief complaints were also assessed at triage by an RN and were grouped into 53 categories for analysis.…”
Section: Study Protocolmentioning
confidence: 99%
“…17 ESI has been validated for interrater and interinstitution reliability and is endorsed as a best practice by the Agency for Healthcare Research and Quality. 1,[17][18][19] The extent to which the ESI algorithm is used nationally is not known, but in a recent national poll of 300 ED directors in hospitals across the United States, 71% of 127 respondents reported that they used ESI. 20 Because potential charges cannot be calculated for patients who LWBS, the magnitude of lost revenue to the physician is unknown.…”
mentioning
confidence: 99%